2020
DOI: 10.1103/physrevresearch.2.013108
|View full text |Cite
|
Sign up to set email alerts
|

Pairing in the two-dimensional Hubbard model from weak to strong coupling

Abstract: The Hubbard model is the simplest model that is believed to exhibit superconductivity arising from purely repulsive interactions, and has been extensively applied to explore a variety of unconventional superconducting systems. Here we study the evolution of the leading superconducting instabilities of the single-orbital Hubbard model on a two-dimensional square lattice as a function of onsite Coulomb repulsion U and band filling by calculating the irreducible particle-particle scattering vertex obtained from d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 66 publications
1
31
1
Order By: Relevance
“…Since the CT gap magnitude anticorrelates with the equilibrium superconducting T c in both theory and experiments [91,92], such reduction might be favorable to the onset of out-of-equilbrium pairing. Moreover, in a spin-fluctuation-mediated picture, the CT gap closure will be accompanied by a renormalization of the pairing interaction and of the spin fluctuation spectrum [33,93]. A lower CT gap will also increase the exchange interaction and, hence, the characteristic spin fluctuation energy [94].…”
Section: Discussionmentioning
confidence: 99%
“…Since the CT gap magnitude anticorrelates with the equilibrium superconducting T c in both theory and experiments [91,92], such reduction might be favorable to the onset of out-of-equilbrium pairing. Moreover, in a spin-fluctuation-mediated picture, the CT gap closure will be accompanied by a renormalization of the pairing interaction and of the spin fluctuation spectrum [33,93]. A lower CT gap will also increase the exchange interaction and, hence, the characteristic spin fluctuation energy [94].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that RPA-based weak coupling approaches describe certain behavior in Hubbard models remarkably well. For example, systematic studies of the leading pairing instabilities in a 2D square lattice Hubbard model with increasing Coulomb repulsion U found that weak coupling RPA predictions agreed exceptionally well [23] with those of non-perturbative quantum Monte Carlo dynamic cluster approximation (DCA) [24] results. Similarly, for a Hubbard model in a two-leg ladder geometry, RPA calculations within a fluctuation exchange approximation (FLEX) were shown to capture the main features of density matrix renormalization group (DMRG) results for the magnetic and charge dynamical response [25].…”
Section: Introductionmentioning
confidence: 91%
“…Numerical solution of the gap equation shows that the gap function decreases slowly like 1/ω at large ω and is often used at intermediate coupling 28 and at relevant relatively small frequencies can be approximated by its n = 0 component:…”
Section: B the D -Wave Analog Of The Asymptotic Expression For Tcmentioning
confidence: 99%